Digital Education in German Primary Schools. A Challenge for School Leadership. - Dertinger, Andreas; Bärnreuther, Cindy (New Media Pedagogy. Research Trends, Methodological Challenges, and Successful Implementations. Second International Conference., 2024)
Digital literacy is an important part of school education. However, its development and curricular implementation in German elementary schools has been slow. This article uses a qualitative study to examine how the curricular implementation of digital education is currently progressing in German primary schools and what influence the Covid-19 pandemic has had on it. In the study, focus group interviews were conducted with different stakeholders in primary education in Germany in order to combine multiple perspectives on this situation. The results reveal several challenges for German primary schools in implementing digital education. School leadership has an important role to play in addressing these challenges. The development of internal school media concepts proved to be an important tool for promoting digital school development. In contrast, the Covid-19 pandemic had a limited long-term impact on the implementation of digital education in primary schools. More important and sustainable are the digital school development initiatives that the primary school was already pursuing before the pandemic.